2020
DOI: 10.1098/rsos.200845
|View full text |Cite
|
Sign up to set email alerts
|

Judging meaning: A domain-level difference between autistic and non-autistic adults

Abstract: We tested whether autistic adults would show selective difficulties across several tests of inferencing and social understanding in the context of average-range core language ability. One-hundred and ninety-one participants completed an online battery, and data were analysed using confirmatory factor analysis. Results showed that vocabulary knowledge was separate from other measures, which collectively formed a ‘receptive communication' factor. Autistic people underperformed on the ‘receptive communication' fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In later research, an objective multiple-choice version of the task was found to be 'as sensitive as the traditional subjective method in demonstrating the wellestablished mentalizing impairment in autism' (White et al, 2011, p. 152) and this version has since been developed as a 'fast and straight forward measure of ToM [theory of mind] in autistic and neurotypical adults, to be used in future research and clinical settings' . However, recent work sounds a cautionary note about the sensitivity of the Frith--Happé Animations, as a large sample of autistic adults scored lower, but only slightly, on both mentalising and control animations compared to non-autistic adults (Wilson & Bishop, 2020). This is more consistent with a subtle domain-general difficulty in inferring meaning rather than a marked, but isolated, difficulty with mentalising.…”
mentioning
confidence: 86%
“…In later research, an objective multiple-choice version of the task was found to be 'as sensitive as the traditional subjective method in demonstrating the wellestablished mentalizing impairment in autism' (White et al, 2011, p. 152) and this version has since been developed as a 'fast and straight forward measure of ToM [theory of mind] in autistic and neurotypical adults, to be used in future research and clinical settings' . However, recent work sounds a cautionary note about the sensitivity of the Frith--Happé Animations, as a large sample of autistic adults scored lower, but only slightly, on both mentalising and control animations compared to non-autistic adults (Wilson & Bishop, 2020). This is more consistent with a subtle domain-general difficulty in inferring meaning rather than a marked, but isolated, difficulty with mentalising.…”
mentioning
confidence: 86%
“…Outliers will be defined according to the method of Hoaglin & Iglewicz (1987): more than 2.2 times the interquartile range below the first quartile. In previous work, these criteria led to exclusion of approximately 5% of participants, and captured individuals scoring below approximately 50% on the GDT and 70% on the positive control items of the original version of the ICT (Wilson & Bishop, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Participants select which of five written words is synonymous with a target word, under a 12 s time limit. The original version of the GDT and this task showed a moderate correlation in both autistic and non-autistic samples, suggesting they are overlapping measures of core language ability ( Wilson & Bishop, 2019 , 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies should focus on the interactions between the two domains and compare how the reciprocal relationships are manifested in children with or without neurodevelopmental disorders. Using CFA, it is feasible to evaluate the domain-level differences across groups and variabilities within groups (Wilson & Bishop, 2020 , 2021 ). An additional benefit of assessing structural language skills is that their language age can also be estimated so that the obstacle of recruiting chronologically age-matched participants with ASD can also be circumvented.…”
Section: Future Directionsmentioning
confidence: 99%